Ethos Of Education And Welfare Of Muslim Migrants Case Study in Migrant Settlement of Pangkoh, Pulang Pisau Regency, Central Kalimantan Province. - Qodir, Abdul (Journal of Educational, Health and Community Psychology, 2012)
Muslim migrants in Pangkoh society gain much success in education, work, and life as better in the third decade (2002-2011). In first decades (1982-1991), a small population of middle-level education, the primary school majority, started a new life. Migrant population who lives a mediocre gets better in term of theirself and children. Many of them send their children to learn. Education is consideredly urgent and important need for them. Childs success in education is a source of pride to the elderly (Tanya Basok). This study focused on issues of education and welfare ethos, which define: (1) how the ethos phenomenon of Muslim migrants toward education, and (2) how the image of success in educational and welfare ethos in Pangkoh. This research aims to describe and interpret ethos phenomena of education, success, and welfare through perspective of psychology and Islam. This study was descriptive qualitative research, especially related to culture. The approach used is ethnographic research in an effort to understand the ethos of education and achieve welfare of the migrant community of Pangkoh. Subjects were Muslim migrants living in Pangkoh. They are grouped in two sections of migrants namely migrant with secondary education by 12 families, and those with basic education, primary school or an equivalent amounting 11 families. Data collection techniques using primary techniques of in-depth interviews and observations related to the problem. In addition, participant observation is used as a supporting method to observe things that are related to the research objectives. Qualitative data analysis is performed by means of narrative and interpretive descriptions of the phenomenon and welfare ethos that has been found within Muslim migrant families. This study shows that, first, the Muslim migrants who arrived in early 1982 and educated middle or slightly higher in the second decade, increases in number. That is evidenced by number of migrants who took up undergraduate degree for himself and family. In the third decade, the settlers produce groups who graduate and work as civil servants. Main work of some Muslim migrants increased in the career ranks, and the task of leading school. The increase of revenue in the form of allowances and benefits lead to educator certification. Therefore they are able to improve service, including the conduct of worship umrah, hajj, and help the relatives education. Second, the early arrival of Muslim migrants of basic education, primary school or its equivalent, have an indirect educational ethos, in three decades, when the decade I, their pioneering work faced many obstacles, unhappy experience. Ethos of the migrant children studying constrained, due to limited education, transportation, economic conditions are relatively difficult parents. Decade II is marked by increasing efforts have been initiated. They include some of the children helped odd jobs while studying. In the third decade (2002-2011) most of them have successful business. Some of them worked as farmers who are now aging. Their children finish high school, extending college graduate or work. Muslim migrant groups who have basic education are not directly educational ethos, but they produce graduates capable of working. Migrant children claimed their success in the struggle of parents are blessed by Allah SWT. The contribution of this research will develop the ethos of the Muslim migrants for valuable input for local governments Pulang Pisau, and as a true imaging.